2020
DOI: 10.3390/ijerph17062061
|View full text |Cite
|
Sign up to set email alerts
|

A Logic Model for Evaluation and Planning in an Adult Day Care for Disabled Japanese Old People

Abstract: Adult day care (ADC) provides various services for meeting clients’ needs. Based on the mini-Delphi method with 46 ADC staff and the discussions with eight ADC administrators, this study developed and finalized a comprehensive logic model to represent the elements of ADC. For the three basic structures of a logic model—inputs/activities, outputs, and outcomes—the model contained seven core categories and 23 sub-categories. The ADC inputs/activities consisted of two core categories: “Place to stay” and “Interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(26 reference statements)
0
10
0
1
Order By: Relevance
“…These services are heterogeneous and range from daily activities, such as meal and snack provision and bathing, to interventional activities, such as exercising, games, hobbies and rehabilitation. About 12% of the aged population in Japan used one or more LTC service in April 2018 [ 52 ]. National LTC insurance covers LTC services and people who are not fully independent (over 97% of those reported in the study were 65 years or over) can use the LTC services under this insurance fee coverage [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These services are heterogeneous and range from daily activities, such as meal and snack provision and bathing, to interventional activities, such as exercising, games, hobbies and rehabilitation. About 12% of the aged population in Japan used one or more LTC service in April 2018 [ 52 ]. National LTC insurance covers LTC services and people who are not fully independent (over 97% of those reported in the study were 65 years or over) can use the LTC services under this insurance fee coverage [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…National LTC insurance covers LTC services and people who are not fully independent (over 97% of those reported in the study were 65 years or over) can use the LTC services under this insurance fee coverage [ 40 ]. In 2020, the number of daycare service clients was 1.13 million and daycare was the most popular service among the population using LTC services [ 52 ]. One international review demonstrated that daycare service providers had the following general aims: (i) providing social and preventive services, (ii) supporting clients’ continued independence and (iii) supporting attendees’ health and daily living needs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ADC logic model [ 13 ] has 10 subcategories for clients’ experiences (8 separate ones, and 2 for clients and their family members) regarding ADC service use. Relying on the ADC logic model, the first author read the raw data of previous research in which the model was developed.…”
Section: Methodsmentioning
confidence: 99%
“…At the beginning of the CRAQ, the logic model of ADC service use was described ( Figure A1 ) [ 13 ]; it was a systematic chart with service input/activity elements and clients’ outcomes. The inputs had two aspects: place and intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation